2012
DOI: 10.1177/0040517512447586
|View full text |Cite
|
Sign up to set email alerts
|

A new method of yarn hairiness reduction by air suction during carding

Abstract: Yarn hairiness has remained an issue of enormous interest in the field of yarn spinning research, since it directly affects yarn quality. In this work, a new method for the reduction of yarn hairiness is presented by attaching a simple effective air suction system to the web detaching zone of a conventional carding machine immediately behind crushing rollers. The slivers produced were almost free from dust or short loose fibers. Yarn properties such as hairiness, tenacity, elongation at break and evenness were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Filament yarn can be produced easily as compared to spun yarn, which undergoes different operations to be made from the staple fibers. e quality and type of yarn has an impact on product quality, performance, and cost [16][17][18]. e second step is to obtain a fabric that is a plane-like structure produced from the yarns or fibers directly.…”
Section: Textile Assembliesmentioning
confidence: 99%
“…Filament yarn can be produced easily as compared to spun yarn, which undergoes different operations to be made from the staple fibers. e quality and type of yarn has an impact on product quality, performance, and cost [16][17][18]. e second step is to obtain a fabric that is a plane-like structure produced from the yarns or fibers directly.…”
Section: Textile Assembliesmentioning
confidence: 99%
“…Apart from the available compact spinning systems which considerably reduce yarn hairiness by eliminating the spinning triangle during yarn formation, many researchers have made efforts to reduce hairiness of cotton yarns by modifications to conventional spinning machines. Mirzaei et al [95] suggested a new and simple method for reduction of yarn hairiness by attaching an air-suction system to the web-detaching zone of a conventional carding machine immediately behind the crushing rollers. The ringspun yarn produced using this system was called vacuum-cleaned carded yarn and showed a 20% improvement in yarn hairiness along with improvement in yarn evenness, tenacity and elongation at break.…”
Section: 22mentioning
confidence: 99%
“…Mirzaei et al proposed a modification to carding to remove short fibers from the surface of the carding web. 66 Special perforated suction rollers were installed on a carding machine after the doffer for removal of short fibers. The yarns made from this system are called VCC (vacuum clean carded) yarns and exhibited significant improvements in quality over conventional carded yarns especially in terms of hairiness.…”
Section: Modifications In Conventional Spinning Machines For Hairiness Reductionmentioning
confidence: 99%